The Effect Of Training And Facilities On Employee Work Productivity At The Gumay Talang Sub-District Office, Lahat Regency - Sintia Ulandari; Heri Fitriadi; Nidyawati Nidyawati (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
From the calculation of the regression coefficient, the equation y = 28,089 + 0.013 X1 + 0.303 + e is obtained, Leadership has a positive influence on the Work Productivity of Employees at the Gumay Talang Sub-district Office, Lahat Regency. The conclusion is because F sig > 0.05 (0.396 > 0.05) This means that together Training and Facilities have a significant effect on the Work Productivity of Employees at the Gumay Talang Sub-district Office, Lahat Regency. From the results of the table above, it can be seen that H1 is accepted F count (0.396) > F table (0.05). For Partial calculations, it can be concluded that the t count for the Training variable (X1) of 0.015 is greater than the t table of 0.05 (0.015 <0.05), thus the Training variable has a significant influence on the Work Productivity of Employees at the Gumay Talang Sub-district Office, Lahat Regency, which means H1 is accepted Ho is rejected. or Partial Calculation, it can be concluded that the calculated t-value for the Facilities variable (X2) is 0.351, which is greater than the t-table value of 0.05 (0.351 > 0.05). Thus, the Facilities variable has a significant influence on the Work Productivity of Employees at the Gumay Talang Sub-district Office, Lahat Regency. The coefficient of determination (R2) is 0.249, indicating that the Training and Facilities variables contribute 62% to Employee Work Productivity, while the remaining 38% is explained by factors outside the study.